Representasi Tanggung Jawab Keluarga dalam Film “1 Kakak 7 Ponakan”: Kajian Semiotika Ferdinand De Saussure - Fadila Fatin; Nurtiarah Nurtiarah; Lia Mauliana; Dinda Puja Andari; Bungsu Keumalasari (Indo Publishing, 2026)
This study aims to analyze the representation of family responsibility in the film 1 Kakak 7 Ponakan using Ferdinand de Saussure's semiotic theory. This research employs a descriptive qualitative approach with documentation as the data collection technique. Data were obtained from scenes, dialogues, character expressions, and visual symbols throughout the film. Analysis was conducted by identifying the signifier and signified in each scene, then connecting both elements to reveal the meaning of family responsibility. The findings show that family responsibility is represented through six major forms: sacrifice of personal interests, caregiving and protection, economic fulfillment, health-priority decision-making, emotional support and family solidarity, and gratitude for shared struggle. The main character, Moko, is depicted as an older sibling who takes on a parental role for his seven nephews and nieces. This study concludes that Ferdinand de Saussure's semiotics is effective in uncovering deeper meanings behind visual and verbal signs in film.